Step 1: The given integral can be written as:
\[
I = \int e^x \left( \frac{x}{\sqrt{1+x^2}} + \frac{1}{(1+x^2)^{\frac{3}{2}}} \right) dx
\]
Let:
\[
f(x) = \frac{x}{\sqrt{1+x^2}}
\]
Step 2: Now, calculate the derivative of \( f(x) \):
\[
f'(x) = \frac{\sqrt{1+x^2} - \frac{x \cdot x}{\sqrt{1+x^2}}}{1+x^2}
= \frac{\sqrt{1+x^2} - \frac{x^2}{\sqrt{1+x^2}}}{1+x^2}
\]
Simplify the numerator:
\[
f'(x) = \frac{\sqrt{1+x^2} - \frac{x^2}{\sqrt{1+x^2}}}{1+x^2} = \frac{1}{(1+x^2)^{\frac{3}{2}}}
\]
Thus, the integral becomes:
\[
I = \int e^x \left( f(x) + f'(x) \right) dx
\]
Step 3: Using the standard result:
\[
\int e^x \left( f(x) + f'(x) \right) dx = e^x f(x) + C
\]
Substitute \( f(x) = \frac{x}{\sqrt{1+x^2}} \):
\[
I = e^x \frac{x}{\sqrt{1+x^2}} + C
\]
\subsection*{Final Answer:}
\[
\boxed{I = e^x \frac{x}{\sqrt{1+x^2}} + C}
\]
\subsection*{Explanation:}
1. Splitting the Integral: The given integral is split into terms containing \( \frac{x}{\sqrt{1+x^2}} \) and \( \frac{1}{(1+x^2)^{\frac{3}{2}}} \).
2. Defining \( f(x) \): The function \( f(x) \) is chosen as \( \frac{x}{\sqrt{1+x^2}} \) because its derivative results in the second term, \( \frac{1}{(1+x^2)^{\frac{3}{2}}} \).
3. Applying the Formula: The integral formula for \( \int e^x (f(x) + f'(x)) dx = e^x f(x) + C \) is directly applied.
4. Substitution: Finally, substituting \( f(x) \) into the formula gives the result.